Studies on the Euglycemic and Hypolipidemic Potentials of the Novel Indole Analogue of Thiazolidinedione, DRF 2189 - Chakrabarti, Ranjan; Vikramadithyan, Reeba Kannimel; Dileepkumar, Tripuraneni; Sunil Kumar, Kochunarayanapillai Bhadramma; Prem Kumar, Mamnoor; Misra, Parimal; Bheema Rao, Paraselli; Lohray, Vidya Bhusan; Lohray, Braj Bhusan; Rajagopalan, Ramanujam (Arzneimittelforschung, 1999)
Euglycemic and hypolipidemic activities of a novel indole analogue of thiazolidinedione, DRF 2189 (CAS 172647-53-9), have been evaluated in different animal models. Compared to troglitazone (CAS 97322-87-7), DRF 2189 exhibited interesting plasma glucose and triglyceride lowering activity in genetically diabetic and obese db/db mice. It also produced a significant reduction in plasma glucose, triglyceride, total cholesterol levels and improvement in oral glucose tolerance in another genetic mouse model, the ob/ob mice. In high-fat diet fed Sprague-Dawley rats, DRF 2189 treatment showed improvement in plasma lipid parameters. Like other thiazolidinediones, this compound also possesses peroxisome proliferator activated receptor gamma (PPARγ) transactivation potential. In anaesthetized rat experiment, DRF 2189 produced a transient fall in blood pressure without any change in the ECG pattern. It showed non-specific smooth muscle relaxant activity against acetylcholine, histamine and potassium chloride induced contractions in isolated guinea pig ileum. A twenty-eight-day toxicity study in Wistar rats did not show any signs of treatment related adverse effects. The overall antidiabetic and hypolipidemic activities of DRF 2189 are comparable with rosiglitazone (CAS 155141-29-0) and superior to troglitazone. In conclusion, results from these preclinical studies indicate that DRF 2189, a novel thiazolidinedione, has a marked potential for the management of type-2 diabetes.
Keywords: CAS 172647-53-9; DRF 2189, euglycemic activity, hypolipidemic activity; 5-[4-[2-(1-Indolyl)ethoxy]phenylmethyl]thiazolidine-2,4-dione; Insulin sensitizer